Diversity of bdelloid rotifer in wetland and lakes of Sôya Coast, East Antarctica - Wada, Tomotake; Kudoh, Sakae (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OB] Polar Biology, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object